2020
DOI: 10.4062/biomolther.2020.113
|View full text |Cite
|
Sign up to set email alerts
|

Fangchinoline Has an Anti-Arthritic Effect in Two Animal Models and in IL-1β-Stimulated Human FLS Cells

Abstract: Fangchinoline (FAN) is a bisbenzylisoquinoline alkaloid that is widely known for its anti-tumor properties. The goal of this study is to examine the effects of FAN on arthritis and the possible pathways it acts on. Human fibroblast-like synovial cells (FLS), carrageenan/kaolin arthritis rat model (C/K), and collagen-induced arthritis (CIA) mice model were used to establish the efficiency of FAN in arthritis. Human FLS cells were treated with FAN (1, 2.5, 5, 10 μM) 1 h before IL-1β (10 ng/mL) stimulation. Cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, numerous lines of evidence have revealed that Fan induces autophagy via the activation of AMPK/mTOR/ULK1 signaling pathway ( Xiang et al, 2021 ). Meanwhile, Fan has also been reported to inhibit the PI3K/Akt and MAPK signaling pathways in several diseases ( Li et al, 2017 ; Jiang F. et al, 2020 ; Chen et al, 2020 ; Villa et al, 2020 ; Chen et al, 2022 ). However, the exploration of Fan’s impact on proteasome regulation remains relatively limited and restricted to human cancer cells and articular chondrocytes ( Chuu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, numerous lines of evidence have revealed that Fan induces autophagy via the activation of AMPK/mTOR/ULK1 signaling pathway ( Xiang et al, 2021 ). Meanwhile, Fan has also been reported to inhibit the PI3K/Akt and MAPK signaling pathways in several diseases ( Li et al, 2017 ; Jiang F. et al, 2020 ; Chen et al, 2020 ; Villa et al, 2020 ; Chen et al, 2022 ). However, the exploration of Fan’s impact on proteasome regulation remains relatively limited and restricted to human cancer cells and articular chondrocytes ( Chuu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fan has been demonstrated to possess significant anti-inflammatory properties in various inflammatory diseases. Notably, Fan has been shown to exert anti-arthritic effects via the inhibition of MAPK pathway and NF-κB pathway in cell and animal models of rheumatoid arthritis ( Villa et al, 2020 ). Meanwhile, Fan has exhibited the ability to attenuate LPS-induced endotoxemia by inhibiting ERK1/2 and NF-κB p65 phosphorylation ( Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rats were induced with arthritis using C/K by following a protocol as described ( Hwang et al ., 2008 ; Villa et al ., 2020 ). 3% Isoflurane in N 2 O/O 2 mixture was used to anesthetize the rats, and an intra-articular injection of 100 μL of 5% C/K suspended in saline into the left knee joint was performed to induce arthritic inflammation.…”
Section: Methodsmentioning
confidence: 99%